(untitled) (Journal of Enam Medical College, 2012)
Background: Masses in the neck are very common and these may range from inflammatory to neoplastic lesions. Fine needle aspiration cytology (FNAC) is a simple, quick and minimally invasive procedure that is well recognized and widely accepted diagnostic tool in separating inflammatory lesions from cystic and neoplastic lesions of the neck. We designed this study in our populations for evaluation of FNAC of different neck masses and that might facilitate the diagnosis and management of these lesions. Objectives: To find out the frequency of different pathological conditions detected on FNAC, to determine the prevalence of neck masses with respect to age and sex and to assert their organs of origin and the nature of the lesions. Materials and Methods: This study was conducted in the Department of Pathology, Enam Medical College, Savar, Dhaka from January 2009 to August 2010. The patients of any age and either sex with neck masses were included. Total 526 patients with neck swellings were included in this study. Among these 60.6% were females and 39.4% were males with male to female ratio of 1:1.54. The age of the patients ranged from 10 months to 85 years with mean age of 32.52 ±17.01 years. Results: Of the 526 cases 341 (64.8%) were from lymph nodes, 127 cases (24.2%) from thyroid glands, 32 cases (6.1%) from salivary glands, 14 cases (2.7%) from cysts and 12 cases (2.2%) from soft tissues. FNAC revealed that 86.2% of the lesions were non-malignant which included 60.5% of inflammatory lesions and 25.7% of other benign lesions. Malignant lesions were found in 8% of cases and 5.9% of the cases were categorized as indeterminate follicular neoplasm of the thyroid gland. Conclusion: Reactive lymphadenitis is the commonest condition in the neck swellings followed by tuberculous lymphadenitis, nodular goiter and malignant neoplasm, especially metastatic carcinoma. DOI: http://dx.doi.org/10.3329/jemc.v1i1.11131 J Enam Med Col 2011; 1(1): 8-14